Hubungan Antara Motivasi Belajar Dengan Prestasi Belajar Mahasiswa/i Fakultas Kedokteran Universitas HKBP Nommensen - Henny Erina Saurmauli Ompusunggu (Nommensen Journal of Medicine, 2020)
Background : Quality human resource are needed by our country in order to compete with other countries. Indicator of quality human resources graduated from university are good academic achievements. Academic achievement is affected by several factors, such as learning motivation. The aim of this study is to determine the correlation between learning motivation and academic achievements in Medical Faculty of Universitas HKBP Nommensen students. Methods: This research was an analytic study. Respondents of this study were 148 active students of Universitas HKBP Nommensen. Learning motivation skor were obtained using an intrinsic motivation questionnaire and academic achievements were obtained from cumulative achievement index. Pearson test was used to analyzed the correlation between learning motivation and academic achievements of respondents. Results: Medical Faculty of Universitas HKBP Nommensen students majority had high learning motivation with academic achievments 3,19 ± 0,28. There was no correlation between learning motivation and academic achievements in Medical Faculty of Universitas HKBP Nommensen students (p = 0,227). Conclusion: There is no correlation between learning motivation and academic achievements in Medical Faculty of Universitas HKBP Nommensen students.